BENGALI PROVERBS PREVALENT IN ASSAM: INTERNAL DIALECTIC OF THE CONTEXT FAMILY - Haque, Imdadul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Marxist thought continues to identify the dialectical relationship behind the evolution of civilization. It is said that the family was later born from the ruins of early group life and that the above-mentioned Marxist dialectical thinking lies behind the movement of that family. The essence of this is to show the social reality of that dilemma by citing the example of the Bengali proverb of Assam